Problems of siliceous rock terminology in Croatian archaeology - Šošić Klindžić, Rajna (Array, 2010)
This paper will give a short overview on the problems concerning terminology of siliceous rocks in archaeological context in Croatian language. Short history of the use of specific terms will be presented, as well as some discrepancies in use of certain terms in archaeological and geological context.